2017
DOI: 10.1097/jom.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and the Performing Arts

Abstract: Treatment providers have a history of involvement with segments of the performing arts. The occupational health approach to workplace health issues can effectively complement these efforts. Sources of further information on performing arts health concerns are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 136 publications
0
5
0
1
Order By: Relevance
“…2,22 Second, rapid bone growth compared with that of the connective tissues initiates a decrease in motor ability and dynamic balance, 23 and learned motor patterns become unreliable. 24,25 Third, load and strain on muscles and ligaments increase due to the vulnerability of a young dancer's musculoskeletal system, 4,13,26 which has been shown to cause a higher prevalence of injury. 27 Finally, dancing prematurely en pointe could prevent the closure of ossification centers of the foot, 4,10,28 as complete ossification in the feet does not occur until around 18 years of age.…”
Section: Age Growth and Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…2,22 Second, rapid bone growth compared with that of the connective tissues initiates a decrease in motor ability and dynamic balance, 23 and learned motor patterns become unreliable. 24,25 Third, load and strain on muscles and ligaments increase due to the vulnerability of a young dancer's musculoskeletal system, 4,13,26 which has been shown to cause a higher prevalence of injury. 27 Finally, dancing prematurely en pointe could prevent the closure of ossification centers of the foot, 4,10,28 as complete ossification in the feet does not occur until around 18 years of age.…”
Section: Age Growth and Injurymentioning
confidence: 99%
“…2,6,11 Anatomically, dancers should encompass an array of physical attributes to perform en pointe correctly and safely. 1,2 Dancers are required to demonstrate adequate and stable ankle ROM 1,6,7 (plantar flexing the foot in parallel with the tibia), strong tendu (extending the foot of the working leg across the floor to pointe while the other foot supports weight), adequate strength and alignment in the core and lower extremities, 12,13 and 90° to 100° of plantar flexion at the ankle during relevé. 1,2,4,14 Subsequently, it has been suggested that dancers require at least 2 years of ballet experience prior to going en pointe, 12,13 and pointe training should be discouraged for dancers who are only doing one ballet class a week or have reduced ROM of the ankles and feet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focusing on the viewpoint of occupational health and safety explore injuries of arts performers. The findings imply that workplace and environment hazards cause musculoskeletal injuries and disabilities (Charlene Angela, 2018;Hinkamp et al, 2017;Leaver et al, 2011;Raymond et al, 2012;Shah et al, 2012) and mental health disorders (e.g. depression and anxiety; Leaver et al, 2011;Raymond et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Stage performers have a high risk of suffering from occupational health problems [30]. Especially for the performing arts which require high-quality visual effects, actors might need to wear heavy makeup frequently to achieve such effects and are therefore heavily exposed to cosmetics [25].…”
Section: Introductionmentioning
confidence: 99%